The effects of cosmetic care on body image, social avoidance and distress in young Chinese breast cancer patients receiving chemotherapy - Shengqun Hou; Zhenqi Lu; Jiajia Qiu; Xiaoju Zhang; Jialing Huang; Yun Li; Cuixia Fu (Clinical and Experimental Obstetrics & Gynecology)
Background: This study aimed to explore the effects of cosmetic care on body image (BI), and social avoidance and distress (SAD) in young Chinese breast cancer patients, aged 18–40 years old, receiving adjuvant chemotherapy. Methods: This was a 2-arm quasi-experimental study based on a single-center. A convenience sample of 76 hospitalized young female breast cancer patients, stage 0-III breast cancer diagnosis was recruited. The control group received usual care, while cosmetic care was added to the intervention group. The primary outcomes were BI and SAD accompanying chemotherapy, and the secondary outcome was the appearance satisfaction. It was registered at Clinical Trials.gov, no. NCT04733482. Results: There were significant differences in patients’ body image, and social avoidance and distress scores from the pre-discharge (T0) to at the end of the chemotherapy cycle (T2) between two groups (P < 0.05). However, the intervention did not significantly change the appearance satisfaction at T2 (P > 0.05). Logistic regression suggested there were no confounding demographic factors influencing the intervention. Conclusions: The present study indicated that cosmetic care improved BI and reduced SAD in young Chinese breast cancer patients during adjuvant chemotherapy. However, a randomized study should be undertaken to confirm our results.